Major metropolis rail system access to dental care for the retired and elderly: a high‐resolution geographic study of Sydney, Australia. (14th November 2014) - Zainab, Uswa‐I; Kruger, Estie; Tennant, Marc
Abstract : Objective: This study examined the spatial accessibility of the Sydney Dental Hospital, to the people of metropolitan Sydney, using a geographic information systems approach. Background: Sydney, Australia's largest city and the state capital of New South Wales, has 4.6 million people, with one‐fifth of the Australian population (4.6 million people). Public dental services exist, but accessibility is limited to some specific population groups, who meet specific eligibility criteria. Methods: All adults (those older than 15 years) were included in the study, and two subsets of this population, retirees (older than 65 years) and elderly (older than 85 years), were also examined according to their proximity to the Sydney Dental Hospital, which is located immediately adjacent to the central train station. Census data (population data) and train station geo‐coding data were integrated with high‐resolution geographic information systems to analyse population spatial accessibility. Results: Irrespective of the socioeconomic status, it was found that 43% of all the adults, 42.5% of the retirees and 41.6% of elders lived 2 km away from the nearest train station. Two‐thirds of those in lower socioeconomic status lived within 2 km of a train station, whilst half of those in the higher socioeconomic status groups lived within 2 km from a train station. Conclusion: Metropolitan Sydney is an example of good urban planning where train stations are appropriately placed in high population density and low socioeconomic areas. The same should be investigated in other major metropolises, especially those still in growth and planning transportation systems.